A composite corrosion and scale inhibitor and preparation method thereof

By modifying the composite corrosion inhibitor of aspartic acid and other compounds, the problem of difficult to inhibit specific scale and water source pollution in the prior art is solved, and efficient scale inhibition and environmental protection effects are achieved.

CN119080277BActive Publication Date: 2025-02-07SHAANXI HUATIAN ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411547188.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-02-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

In the prior art, scale inhibitors are difficult to effectively inhibit the precipitation of calcium phosphate scale, zinc scale and iron oxide, and phosphorus-containing compounds are easy to nourish bacterial algae, resulting in water pollution. It is necessary to develop low-phosphorus or phosphorus-free, environmentally friendly green scale inhibitors. agent.

Method used

Combined corrosion inhibitors are prepared by modified aspartic acid and 2-phosphonic acid butane, maleic anhydride, zinc salt, tungstate and azole compounds. Through copolymerization and microwave treatment, scale resistance is enhanced and phosphorus content is reduced.

Benefits of technology

Effective inhibition and dispersion of calcium phosphate scale, iron oxide, manganese deposits and mud particles is achieved, delaying scale formation, enhancing scale resistance, and reducing phosphorus content to achieve environmentally friendly results.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite corrosion and scale inhibitor and a preparation method thereof, and relates to the technical field of circulating water scale inhibition. The invention utilizes malic acid, sodium allyl sulfonate and aspartic acid for blending and modification, and promotes the reaction and polymerization of each monomer under the action of microwaves, thereby achieving the effects of scale inhibition and corrosion inhibition, while a large number of carboxylate ions in the copolymer molecules enhance the scale inhibition performance of the preparation by delaying the formation of scaling, and then, by adding furfurylamine, a heterocyclic group is introduced into the copolymer, and this heterocyclic structure can react with the iron element in the carbon steel material to form a dense pre-film on the surface of the carbon steel, and can cooperate with the carboxylate ions to be fully adsorbed on the surface of calcium carbonate crystals, enhancing the scale inhibition effect of the preparation, and then compounding with a small amount of 2-phosphonic acid-1,2,4-tricarboxylic acid butane to achieve low phosphorus and environmental protection while efficiently enhancing the corrosion and scale inhibition effect of the preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of circulating water scale inhibition, in particular to a composite corrosion and scale inhibitor and a preparation method thereof. Background Art

[0002] Industrial water consumption is huge, and it is bound to be the first to face serious challenges. Among the industrial water consumption, cooling water accounts for a large proportion. Almost all kinds of industrial enterprises need to use cooling water. The cooling water consumption in the petroleum, chemical, electric power, metallurgy and other industries accounts for more than 85% of the total water consumption. A few decades ago, my country adopted a direct cooling water system, which caused a great waste of water resources. In recent years, the circulating cooling water system has been widely promoted in all walks of life because of its obvious water-saving effect. Among them, the open circulating cooling water system is the most widely used. Compared with the direct cooling water system, the fresh water supplemented by this system is generally only about 1 / 40 of the direct water consumption, which can save a lot of cooling water consumption and reduce the amount of sewage discharge accordingly.

[0003] In cooling water systems, scaling of heat exchangers, pipelines, pumps and valves is very common. Scale will reduce the cooling effect of cooling water, shorten the service life of equipment, accelerate metal corrosion, increase maintenance costs, and threaten the safe operation of equipment, resulting in huge economic losses. Among them, corrosion inhibitors are an effective method to control metal corrosion in cooling water. Their advantages are that the dosage is low, generally less than 1%, and the properties of the corrosive medium after addition are basically unchanged. The cost is low and basically no additional investment in anti-corrosion equipment is required. It is also easy to use. At present, organic phosphonic acid, organic polyphosphate and its salts are the most widely used scale inhibitors, such as ATMP, HEDP, PBTCA, etc. However, organic phosphine cannot effectively inhibit calcium phosphate scale, zinc scale and iron oxide precipitation, and phosphorus-containing compounds are easy to nourish bacteria and algae, causing eutrophication of environmental water bodies, thereby causing water pollution. At present, their discharge has been restricted. Therefore, it is particularly necessary to develop low-phosphorus or phosphorus-free, environmentally friendly green scale inhibitors. Summary of the invention

[0004] The purpose of the present invention is to provide a composite corrosion inhibitor and scale inhibitor and a preparation method thereof to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: a composite corrosion inhibitor and scale inhibitor, which is prepared by compounding modified aspartic acid with 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc salt, tungstate, and azole compounds.

[0006] Furthermore, the modified aspartic acid is prepared by mixing and modifying malic acid, sodium allyl sulfonate and aspartic acid.

[0007] Furthermore, a method for preparing a composite corrosion inhibitor and scale inhibitor comprises the following preparation steps:

[0008] (1) Aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water are mixed and subjected to microwave treatment at a power of 500-1000 W for 10-15 min, followed by standing for reaction for 2-4 h, adjusting the solution pH to 7-8 with sodium hydroxide, adding a mixed acid solution for dehydration at a temperature of 150-190° C. for 100-200 min, and then washing with deionized water for 3-5 times, and drying at 25-40° C. and a vacuum degree of 0.2-1 kPa for 15-25 h to obtain modified aspartic acid;

[0009] (2) Modified aspartic acid, furfurylamine and deionized water were mixed, heated to 50-70°C, stirred at 300-600 rpm, and 10 wt% sodium hydroxide aqueous solution was added dropwise at 0.5 mL / s until the solution changed color. The mixture was allowed to react for 24 h. The pH of the solution was adjusted to 7-8 with hydrochloric acid. Anhydrous ethanol was then added dropwise at 0.5 mL / s. The mixture was allowed to react for 6-10 h. The supernatant was removed and the solid was taken. The solid was dried at 25-40°C and a vacuum degree of 0.2-1 kPa for 15-25 h to obtain intermediate A.

[0010] (3) An azole compound, sodium hydroxide, toluene and deionized water are mixed, and then intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc salt and tungstate are added to obtain a composite corrosion inhibitor.

[0011] Furthermore, the mixed acid solution in step (1) is prepared by mixing sulfuric acid, phosphoric acid and deionized water in a mass ratio of 1:1:4-8.

[0012] Furthermore, in step (1), the mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 3-6:0.1-1:2-5:0.2:2:3:0.4.

[0013] Furthermore, in step (2), the mass ratio of the modified aspartic acid, furfurylamine, deionized water and anhydrous ethanol is 1:0.8:10:40-60.

[0014] Furthermore, the azole compound in step (3) is specifically methyl benzotriazole.

[0015] Furthermore, the zinc salt in step (3) is specifically zinc sulfate.

[0016] Furthermore, the tungstate in step (3) is specifically potassium tungstate.

[0017] Furthermore, in step (3), the mass ratio of the azole compound, sodium hydroxide, toluene, deionized water, intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc salt, and tungstate is 3~4.5:0.8~1.5:0.5~1:15:10~20:0.1:2:5~7:1.5~2.

[0018] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0019] The invention utilizes malic acid, sodium allyl sulfonate and aspartic acid for blending and modification, wherein the carboxyl group in the malic acid undergoes an amidation reaction with the amino group in the aspartic acid molecule, and then copolymerizes with the sulfonic acid group in the sodium allyl sulfonate. Under the assistance of microwave action, more free radicals are generated, which is beneficial for each monomer to fully participate in the reaction and polymerize. The introduction of the sulfonic acid group can enhance the solubility of the copolymer, thereby effectively preventing the formation of insoluble calcium gel, and also having a good inhibitory and dispersing effect on calcium phosphate scale, iron oxide, manganese deposits and slime particles, thereby achieving the effect of scale inhibition and corrosion inhibition. At the same time, a large number of carboxylate ions in the copolymer molecules can undergo Coulomb electrostatic interaction with positively charged calcium ions, thereby hindering the carbonate ions in the solution from being formed. Further deposition of scale crystal growth surface, thereby enhancing the scale inhibition performance of the preparation by delaying the formation of scale. Then, by adding furfurylamine, heterocyclic groups are introduced into the copolymer. This heterocyclic structure can react with the iron element in the carbon steel material to chelate and prevent it from becoming trivalent iron ions, so that the preparation can form a dense pre-film on the surface of carbon steel in the circulating water to prevent further corrosion of the metal. It can also cooperate with carboxylate ions to be fully adsorbed on the surface of calcium carbonate crystals, and its regular and neat hexagonal shape is gradually destroyed, thereby enhancing the scale inhibition effect of the preparation. Then, a complex system is formed with a small amount of 2-phosphonic acid-1,2,4-tricarboxylic acid butane to achieve low phosphorus and environmental protection while efficiently enhancing the corrosion and scale inhibition effect of the preparation. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0021] In order to more clearly illustrate the method provided by the present invention, the following examples are used to describe in detail the various index testing methods of the composite corrosion inhibitor and scale inhibitor prepared in the following examples are as follows:

[0022] Corrosion inhibition performance: Take the same size of the embodiment and the comparative example according to GB / T18175, the carbon steel test piece is 20 #The test temperature is 45°C, the rotation speed is 90rpm, and the time is 72h to detect its corrosion rate.

[0023] Scale inhibition performance: The same size of the embodiment and the comparative example were taken and tested for calcium carbonate scale inhibition performance according to GB / T16632. The test temperature was 80°C and the test time was 10 hours.

[0024] Example 1; (1) sulfuric acid, phosphoric acid and deionized water were mixed in a mass ratio of 1:1:4 to obtain a mixed acid solution; aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water were mixed and subjected to microwave treatment at a power of 500 W for 10 min, followed by standing for 2 h, adjusting the solution pH to 7 with sodium hydroxide, adding the mixed acid solution for dehydration at a temperature of 150 ° C for 100 min, and then washing with deionized water 3 times at 25 ° C, The vacuum degree is 0.2kPa Down Dry for 15 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 3:0.1:2:0.2:2:3:0.4;

[0025] (2) Modified aspartic acid, furfurylamine and deionized water were mixed, heated to 50°C, stirred at 300 rpm, and 10 wt% sodium hydroxide aqueous solution was added dropwise at 0.5 mL / s until the solution changed color. The solution was allowed to react for 24 h. The pH of the solution was adjusted to 7 with hydrochloric acid, and anhydrous ethanol was added dropwise at 0.5 mL / s. The solution was allowed to react for 6 h. The supernatant was removed and the solid was taken. The mixture was heated to 25°C. The vacuum degree is 0.2kPa Down Dry for 15 hours to obtain intermediate A; the mass ratio of the modified aspartic acid, furfurylamine, deionized water and anhydrous ethanol is 1:0.8:10:40;

[0026] (3) Mix methylbenzyltriazole, sodium hydroxide, toluene and deionized water, and then add intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate to obtain a composite corrosion inhibitor and scale inhibitor; the mass ratio of methylbenzyltriazole, sodium hydroxide, toluene, deionized water, intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate is 3:0.8:0.5:15:10:0.1:2:5:1.5.

[0027] Example 2; (1) sulfuric acid, phosphoric acid and deionized water were mixed in a mass ratio of 1:1:6 to obtain a mixed acid solution; aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water were mixed and subjected to microwave treatment at a power of 700 W for 12 min, followed by standing for 3 h, adjusting the solution pH to 7.5 with sodium hydroxide, adding the mixed acid solution for dehydration at a temperature of 170 ° C for 150 min, and then washing with deionized water 4 times at 33 ° C, The vacuum degree is 0.6kPa Down Dry for 20 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 4.5:0.6:3.5:0.2:2:3:0.4;

[0028] (2) Modified aspartic acid, furfurylamine and deionized water were mixed, heated to 60°C, stirred at 450 rpm, and 10 wt% sodium hydroxide aqueous solution was added dropwise at 0.5 mL / s until the solution changed color. The solution was allowed to react for 24 h. The pH of the solution was adjusted to 7.5 with hydrochloric acid, and anhydrous ethanol was added dropwise at 0.5 mL / s. The solution was allowed to react for 8 h. The supernatant was removed and the solid was taken. The mixture was heated to 33°C. The vacuum degree is 0.6kPa Down Dry for 20 hours to obtain intermediate A; the mass ratio of the modified aspartic acid, furfurylamine, deionized water and anhydrous ethanol is 1:0.8:10:50;

[0029] (3) Mix methylbenzatriazole, sodium hydroxide, toluene and deionized water, and then add intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate to obtain a composite corrosion inhibitor and scale inhibitor; the mass ratio of methylbenzatriazole, sodium hydroxide, toluene, deionized water, intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate is 4:1.2:0.7:15:15:0.1:2:6:1.8.

[0030] Example 3; (1) sulfuric acid, phosphoric acid, and deionized water were mixed in a mass ratio of 1:1:8 to obtain a mixed acid solution; aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, and deionized water were mixed and subjected to microwave treatment at a power of 1000 W for 15 min, followed by standing for 4 h, adjusting the solution pH to 8 with sodium hydroxide, adding the mixed acid solution for dehydration at a temperature of 190 ° C for 200 min, and then washing with deionized water 5 times at 40 ° C, The vacuum degree is 1kPa DownDry for 25 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 6:1:5:0.2:2:3:0.4;

[0031] (2) Modified aspartic acid, furfurylamine and deionized water were mixed, heated to 70°C, stirred at 600 rpm, and 10 wt% sodium hydroxide aqueous solution was added dropwise at 0.5 mL / s until the solution changed color. The solution was allowed to react for 24 h. The pH of the solution was adjusted to 8 with hydrochloric acid, and anhydrous ethanol was added dropwise at 0.5 mL / s. The solution was allowed to react for 10 h. The supernatant was removed and the solid was taken. The mixture was heated to 40°C. The vacuum degree is 1kPa Down Dry for 25 hours to obtain intermediate A; the mass ratio of the modified aspartic acid, furfurylamine, deionized water and anhydrous ethanol is 1:0.8:10:60;

[0032] (3) Mix methylbenzatriazole, sodium hydroxide, toluene and deionized water, and then add intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate to obtain a composite corrosion inhibitor and scale inhibitor; the mass ratio of methylbenzatriazole, sodium hydroxide, toluene, deionized water, intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc sulfate and potassium tungstate is 4.5:1.5:1:15:20:0.1:2:7:2.

[0033] Comparative Example 1: The difference between Comparative Example 1 and Example 2 is that step (1) is different. Step (1) is changed to: sulfuric acid, phosphoric acid and deionized water are mixed in a mass ratio of 1:1:6 to obtain a mixed acid solution; aspartic acid, sodium allyl sulfonate, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water are mixed and subjected to microwave treatment at a power of 700 W for 12 min, followed by standing for reaction for 3 h, adjusting the solution pH to 7.5 with sodium hydroxide, adding the mixed acid solution for dehydration at a temperature of 170°C for 150 min, and then washing with deionized water 4 times at 33°C, The vacuum degree is 0.6kPa Down Dry for 20 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, sodium allyl sulfonate, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 4.5:0.6:0.2:2:3:0.4; the remaining steps are the same as Example 2.

[0034] Comparative Example 2: The difference between Comparative Example 2 and Example 2 is that step (1) is different. Step (1) is changed to: sulfuric acid, phosphoric acid and deionized water are mixed in a mass ratio of 1:1:6 to obtain a mixed acid solution; aspartic acid, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water are mixed and subjected to microwave treatment at a power of 700 W for 12 min, followed by standing for reaction for 3 h, adjusting the solution pH to 7.5 with sodium hydroxide, adding the mixed acid solution for dehydration at a temperature of 170°C for 150 min, and then washing with deionized water 4 times at 33°C, The vacuum degree is 0.6kPa Down Dry for 20 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 4.5:3.5:0.2:2:3:0.4; the remaining steps are the same as in Example 2.

[0035] Comparative Example 3: The difference between Comparative Example 3 and Example 2 is that step (1) is different. Step (1) is changed to: sulfuric acid, phosphoric acid and deionized water are mixed in a mass ratio of 1:1:6 to obtain a mixed acid solution; aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water are mixed, the temperature is raised to 60°C, and the reaction is carried out for 3 hours. The pH value of the solution is adjusted to 7.5 with sodium hydroxide, and the mixed acid solution is added for dehydration at a temperature of 170°C and a time of 150 minutes, and then washed with deionized water 4 times, 33°C, The vacuum degree is 0.6kPa Down Dry for 20 hours to obtain modified aspartic acid; the mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution is 4.5:0.6:3.5:0.2:2:3:0.4; the remaining steps are the same as in Example 2.

[0036] Comparative Example 4: The difference between Comparative Example 4 and Example 2 is that there is no step (1); the remaining steps are the same as Example 2.

[0037] Comparative Example 5: The difference between Comparative Example 5 and Example 2 is that there is no step (2); the remaining steps are the same as Example 2.

[0038] Comparative Example 6: The difference between Comparative Example 6 and Example 2 is that step (3) is different. Step (3) is changed to: methyl benzotriazole, sodium hydroxide, toluene, and deionized water are mixed, and then intermediate A, maleic anhydride, zinc sulfate, and potassium tungstate are added to obtain a composite corrosion inhibitor and scale inhibitor; the mass ratio of methyl benzotriazole, sodium hydroxide, toluene, deionized water, intermediate A, maleic anhydride, zinc sulfate, and potassium tungstate is 4:1.2:0.7:15:15:2:6:1.8; the remaining steps are the same as in Example 2.

[0039] Effect example

[0040] Table 1 below shows the performance analysis results of the composite corrosion and scale inhibitors of Examples 1 to 3 of the present invention and Comparative Examples 1 to 6.

[0041] Table 1

[0042]

[0043] From the comparison of the experimental data of the embodiment and the comparative example in Table 1, it can be found that the present invention utilizes malic acid, sodium allyl sulfonate and aspartic acid for blending modification, wherein the carboxyl group in the malic acid undergoes an amidation reaction with the amino group in the aspartic acid molecule, and then copolymerizes with the sulfonic acid group in the sodium allyl sulfonate. Under the assistance of microwave action, it is beneficial for each monomer to fully participate in the reaction and polymerize, and the introduction of the sulfonic acid group can enhance the solubility of the copolymer, thereby effectively preventing the formation of insoluble calcium gel, achieving the effect of scale inhibition and corrosion inhibition, and at the same time, a large number of carboxylate ions in the copolymer molecules can interact with the positively charged calcium ions to produce Coulomb electrostatic interaction, hindering the solution from The carbonate ions in the scale crystals are further deposited on the growth surface of the scale crystals, thereby enhancing the scale inhibition performance of the preparation. Then, by adding furfurylamine, a chelating reaction occurs with it to prevent the iron in the carbon steel material from becoming trivalent iron ions. At the same time, a dense pre-film can be formed on the surface of the carbon steel in the circulating water to prevent further corrosion of the metal. It can also cooperate with the carboxylate ions to be fully adsorbed on the surface of the calcium carbonate crystals, and its regular and neat hexagonal shape is gradually destroyed, thereby enhancing the scale inhibition effect of the preparation. It is then combined with a small amount of 2-phosphonic acid-1,2,4-tricarboxylic acid butane to form a complex system to achieve low-phosphorus and environmental protection while efficiently enhancing the corrosion and scale inhibition effect of the preparation.

[0044] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a composite corrosion and scale inhibitor, characterized in that: The method comprises the following preparation steps: (1) Aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide and deionized water are mixed and subjected to microwave treatment at a power of 500-1000 W for 10-15 min, followed by standing for reaction for 2-4 h, adjusting the solution pH to 7-8 with sodium hydroxide, adding a mixed acid solution for dehydration at a temperature of 150-190° C. for 100-200 min, and then washing with deionized water for 3-5 times, and drying at 25-40° C. and a vacuum degree of 0.2-1 kPa for 15-25 h to obtain modified aspartic acid; (2) Modified aspartic acid, furfurylamine and deionized water were mixed, heated to 50-70°C, stirred at 300-600 rpm, and 10 wt% sodium hydroxide aqueous solution was added dropwise at 0.5 mL / s until the solution changed color. The mixture was allowed to react for 24 h. The pH of the solution was adjusted to 7-8 with hydrochloric acid. Anhydrous ethanol was then added dropwise at 0.5 mL / s. The mixture was allowed to react for 6-10 h. The supernatant was removed and the solid was taken. The solid was dried at 25-40°C and a vacuum degree of 0.2-1 kPa for 15-25 h to obtain intermediate A. (3) An azole compound, sodium hydroxide, toluene and deionized water are mixed, and then intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc salt and tungstate are added to obtain a composite corrosion inhibitor.

2. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The mixed acid solution in step (1) is prepared by mixing sulfuric acid, phosphoric acid and deionized water in a mass ratio of 1:1:4-8.

3. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The mass ratio of aspartic acid, sodium allyl sulfonate, malic acid, potassium dihydrogen phosphate, N,N-dimethylformamide, deionized water, and mixed acid solution in step (1) is 3-6:0.1-1:2-5:0.2:2:3:0.

4.

4. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The mass ratio of the modified aspartic acid, furfurylamine, deionized water and anhydrous ethanol in step (2) is 1:0.8:10:40-60.

5. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The azole compound in step (3) is specifically methyl benzotriazole.

6. The method for preparing a composite corrosion and scale inhibitor according to claim 1, characterized in that: The zinc salt in step (3) is specifically zinc sulfate.

7. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The tungstate in step (3) is specifically potassium tungstate.

8. The method for preparing a composite corrosion inhibitor and scale inhibitor according to claim 1, characterized in that: The mass ratio of the azole compound, sodium hydroxide, toluene, deionized water, intermediate A, 2-phosphono-1,2,4-tricarboxylic acid butane, maleic anhydride, zinc salt, and tungstate in step (3) is 3~4.5:0.8~1.5:0.5~1:15:10~20:0.1:2:5~7:1.5~2.

9. A composite corrosion and scale inhibitor, characterized in that: Prepared according to any one of claims 1 to 8.